CREATING HARMONIOUSLY DEVELOPED INDIVIDUALS: THE FOUNDATION OF THE FUTURE OF NEW UZBEKISTAN - Khodjalepesov Polat Zinatdinovich; Muratbeva Sabira Bekmurzaevna; Mambetsharipova Gulzada Polatbaevna (Scholar Express Journals, 2025)
The development of a harmoniously developed generation remains a key priority of the country's leadership. Uzbekistan’s ambitious and determined young people are witnessing tangible results of large-scale reforms aimed at their empowerment. President Shavkat Mirziyoyev has emphasized that youth are the backbone of achieving high national goals and building a new Uzbekistan.
Keywords: Uzbekistan; youth development; education reforms